Self-assembly of amino acids toward functional biomaterials - Ren, Huan; Wu, Lifang; Tan, Lina; Bao, Yanni; Ma, Yuchen; Jin, Yong; Zou, Qianli (Beilstein Journal of Nanotechnology, 2021)
Biomolecules, such as proteins and peptides, can be self-assembled. They are widely distributed, easy to obtain, and biocompatible. However, the self-assembly of proteins and peptides has disadvantages, such as difficulty in obtaining high quantities of materials, high cost, polydispersity, and purification limitations. The difficulties in using proteins and peptides as functional materials make it more complicate to arrange assembled nanostructures at both microscopic and macroscopic scales. Amino acids, as the smallest constituent of proteins and the smallest constituent in the bottom-up approach, are the smallest building blocks that can be self-assembled. The self-assembly of single amino acids has the advantages of low synthesis cost, simple modeling, excellent biocompatibility and biodegradability in vivo. In addition, amino acids can be assembled with other components to meet multiple scientific needs. However, using these simple building blocks to design attractive materials remains a challenge due to the simplicity of the amino acids. Most of the review articles about self-assembly focus on large molecules, such as peptides and proteins. The preparation of complicated materials by self-assembly of amino acids has not yet been evaluated. Therefore, it is of great significance to systematically summarize the literature of amino acid self-assembly. This article reviews the recent advances in amino acid self-assembly regarding amino acid self-assembly, functional amino acid self-assembly, amino acid coordination self-assembly, and amino acid regulatory functional molecule self-assembly.
Keywords: amino acids; functional biomaterials; intermolecular interactions; self-assembly